Education of Lithuanian Exiles in Post-War Germany - Pečkus, Kęstutis (Acta Paedagogica Vilnensia, 1996)
The 1944 mass exile of Lithuanians to the West was the act of trying to save not only the life, but the spirit as well. Most of Lithuanians chose Germany as their temporary living place. According to the data of the International Refugee Organization in November 1945 more than 60 thousand Lithuanians were staying in part of Germany taken over by the Western Allies. In American zone in 1945-1945 there was 31 Lithuanian kindergarten, 46 primary schools, 8 pro-gymnasiums. 593 teachers worked in these educational institutions; 4825 attended them. The article analyses activities of Lithuanian educational institutions in exile. When in 1948 the US Congress adapted a Displaced Persons Act, the second wave of Lithuanian emigration started – this time to America.